Reformas necesarias al art. 74 del código civil Ecuatoriano dirigidas a la protección de los bienes muebles de mayor cuantía del desaparecido, que se encuentran bajo decreto de posesión provisional. - PINEDA ROMERO, EDGAR OLMEDO (2011)
The importance and transcendency of the partner-juridical problem of "you Reform necessary to the Art. 74 of the Ecuadorian Civil Code, directed to the protection of the goods furniture of the missing person's bigger quantity that you/they are low ordinance of provisional possession", it is based mainly in the necessity of guaranteeing the right to the property of people that you/they meet with presumption of death for desaparecimiento and that after some years they reappear, and they don't find their goods to be able to continue working or developing some commercial activity; being generated this problem because the Art's legal norm. 74 of the Code Civil ability to the provisional possessors to have the goods furniture; without considering that at the present time they exist goods furniture of more quantity that the properties that should be protected and aided by the Ecuadorian civil legislation. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypotheses, allowing me to support the proposed changes. The content of the thesis is an intellectual contribution of the postulante in the scientific and methodological environment that approaches theoretical and empirically, the protection of the right of people to the identity that this being limited by the Art's legal disposition. 74 of the Civil Code.